Persistent central memory phenotype of circulating Fel d 1 peptide/DRB1*0101 tetramer-binding CD4+ T cells. - Bateman, E; Ardern-Jones, MR; Ogg, G (2006)
BACKGROUND: Although substantial evidence suggests that T cells are important in the pathogenesis of atopic dermatitis (AD), little is known of the differentiation status of CD4+ T cells specific for common environmental allergens. OBJECTIVE: To determine the frequency, differentiation phenotype, and function of circulating allergen-specific CD4+ T cells in adult individuals with severe persistent AD and controls. METHODS: Using tetrameric complexes of an HLA DRB1*0101 restricted epitope from Fel d 1, the major IgE-reactive component of cat dander, we studied ex vivo and cultured T-cell frequency and phenotype in individuals with AD and healthy controls. Cytokine secretion was measured by ex vivo and cultured IFN-gamma, IL-4, and IL-10 enzyme linked immuno-spot analysis. RESULTS: Ex vivo Fel d 1-specific DRB1*0101-restricted CD4+ T cells express high levels of CCR7, CD62L, CD27, and CD28 and proportionately low levels of tissue-specific homing receptors and TH1 and TH2 cytokine production, placing the cells largely within the central memory subgroup. CONCLUSION: Circulating Fel d 1-specific DRB1*0101-restricted CD4+ T cells maintain central memory capacity, consistent with a potential to contribute to persisting clinical atopic disease. CLINICAL IMPLICATIONS: Persisting central memory characteristics of allergen-specific CD4+ T cells in individuals with AD may contribute to chronic disease.